Pharmacological Treatment of Early-Onset Schizophrenia: A Critical Review, Evidence-Based Clinical Guidance and Unmet Needs - Lopez-Morinigo, Javier-David; Leucht, Stefan; Arango, Celso (Pharmacopsychiatry, 2022)
Early-onset schizophrenia (EOS) – onset before age 18 – is linked with great disease burden and disability. Decision-making for EOS pharmacological treatment may be challenging due to conflicting information from evidence and guidelines and unidentified care needs may remain unmet.We searched for systematic reviews, meta-analyses and umbrella reviews of EOS pharmacological treatment published in PubMed over the past 10 years and selected five clinical guidelines from Europe, North-America and Australia. Based on predefined outcomes, we critically compared the evidence supporting EOS-approved drugs in Europe and/or North-America with guidelines recommendations. We also evaluated the coverage of these outcomes to identify unmet needs.One systematic review, nine meta-analyses and two umbrella reviews (k=203 trials, N=81,289 participants, including duplicated samples across selected articles) were retrieved. Evidence supported the efficacy of aripiprazole, clozapine, haloperidol, lurasidone, molindone, olanzapine, quetiapine, risperidone and paliperidone in EOS, all of which obtained approval for EOS either in Europe and/or in North-America. Cognition, functioning and quality of life, suicidal behaviour and mortality and services utilisation and cost-effectiveness were poorly covered/uncovered.Among the antipsychotics approved for EOS, aripiprazole, lurasidone, molindone, risperidone, paliperidone and quetiapine emerged as efficacious and comparably safe options. Olanzapine is known for a high risk of weight gain and haloperidol for extrapyramidal side-effects. Treatment-resistant patients should be offered clozapine. Future long-term trials looking at cognition, functioning, quality of life, suicidal behaviour, mortality, services utilisation and cost-effectiveness are warranted. Closer multi-agency collaboration may bridge the gap between evidence, guidelines and approved drugs.
Keywords: Child; adolescent; schizophrenia; antipsychotics; metanalysis; systematic review